2023
DOI: 10.1093/jas/skad354
|View full text |Cite
|
Sign up to set email alerts
|

Dietary glycine supplementation enhances postweaning growth and meat quality of pigs with intrauterine growth restriction

Wenliang He,
Erin A Posey,
Chandler C Steele
et al.

Abstract: Pigs with intrauterine growth restriction (IUGR) have suboptimum growth performance and impaired synthesis of glycine (the most abundant amino acid in the body). Conventional corn- and soybean meal-based diets for postweaning pigs contain relatively low amounts of glycine and may not provide sufficient glycine to meet requirements for IUGR pigs. This hypothesis was tested using 52 IUGR pigs and 52 litter mates with normal birth weights (NBW). At weaning (21 d of age), IUGR or NBW pigs were assigned randomly to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Notably, GSH is the most important non-enzymatic antioxidant in animals, whereas creatine helps to store ATP in the form of phosphocreatine for physiological processes such as muscle contractions, protein synthesis, and nutrient transport. Emerging evidence indicates that the endogenous synthesis of glycine may not meet the demand of farmed animals (e.g., HSB and growing pigs) under various nutritional and physiological conditions [ 13 , 14 , 27 ]. Although SBM has a balanced profile for most AAs, this feed ingredient contains much less glycine than fishmeal [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, GSH is the most important non-enzymatic antioxidant in animals, whereas creatine helps to store ATP in the form of phosphocreatine for physiological processes such as muscle contractions, protein synthesis, and nutrient transport. Emerging evidence indicates that the endogenous synthesis of glycine may not meet the demand of farmed animals (e.g., HSB and growing pigs) under various nutritional and physiological conditions [ 13 , 14 , 27 ]. Although SBM has a balanced profile for most AAs, this feed ingredient contains much less glycine than fishmeal [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Growing-finishing pigs cannot produce sufficient GSH in the liver, kidneys, and small intestine, when fed SBM-based diets [ 46 ]. Thus, dietary supplementation with 1% glycine to these animals enhanced this synthetic pathway [ 15 ] and whole-body growth [ 27 ], while reducing oxidative stress in their tissues [ 15 ]. Likewise, dietary supplementation with GSH improves the growth, anti-oxidative capacity, disease resistance and gut morphology in juvenile Atlantic salmon [ 33 ], common carp [ 47 ], triploid rainbow trout [ 48 ], shrimp [ 49 ], and crabs [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…The transcriptomic and metabolomic data revealed that both omics KEGG pathways were significantly enriched in glycine, serine, and threonine metabolism, which may be related to tenderness. Glycine is the main structural unit of connective tissue and can bind with collagen protein to enhance the tenderness of meat [32]. Threonine is an important component of myofibrillar protein and collagen protein, which contributes to the increase in tenderness and flavor [33].…”
Section: Discussionmentioning
confidence: 99%